2021
DOI: 10.5999/aps.2020.00668
|View full text |Cite
|
Sign up to set email alerts
|

>Method to prevent cheek depression using an island sternocleidomastoid muscle flap with the middle pedicle as a feeding vessel in immediate reconstruction of the facial nerve with the sural nerve following resection of a parotid gland tumor

Abstract: Many surgeons have demonstrated the validity of sternocleidomastoid muscle flaps for the reconstruction of head and neck tumors. We present a case in which we used an island sternocleidomastoid muscle flap to reconstruct a cheek depression after excision of a malignant parotid tumor. A 44-year-old woman presented with a right malignant parotid tumor. We performed total resection of the parotid gland and facial nerve with the sural nerve and reconstructed the facial nerve and cheek depression with an island ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The middle pedicle, which flows to the middle part of the SCMM, was identified, and ICG fluorography showed that the muscle was stained from the middle pedicle. It was reported that the middle pedicle supplies blood to the entire SCMM in cadavers [13], and we also reported an island SCMM flap technique with only the middle pedicle [14]. The muscle body was dissected in a bipolar manner.…”
Section: Discussionmentioning
confidence: 96%
“…The middle pedicle, which flows to the middle part of the SCMM, was identified, and ICG fluorography showed that the muscle was stained from the middle pedicle. It was reported that the middle pedicle supplies blood to the entire SCMM in cadavers [13], and we also reported an island SCMM flap technique with only the middle pedicle [14]. The muscle body was dissected in a bipolar manner.…”
Section: Discussionmentioning
confidence: 96%
“…These incisions were used for total parotidectomy by some scholars who have conducted procedures on malignant tumors and large-sized masses. 29 However, evidence for such indications is sparse, with relevant retrospective studies involving only a very small number of malignant tumors. Surgical risks include tumor recurrence due to incomplete tumor resection and the inability to perform secondary neck surgery through the same incision.…”
Section: Discussionmentioning
confidence: 99%
“…For malignant tumors of the parotid gland and tumors located deep in the parotid gland and those that are larger in size, the traditional surgical approach is still advocated. These incisions were used for total parotidectomy by some scholars who have conducted procedures on malignant tumors and large-sized masses 29 . However, evidence for such indications is sparse, with relevant retrospective studies involving only a very small number of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%